If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + -17 + z = 13 Reorder the terms: -17 + 3z + z = 13 Combine like terms: 3z + z = 4z -17 + 4z = 13 Solving -17 + 4z = 13 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 4z = 13 + 17 Combine like terms: -17 + 17 = 0 0 + 4z = 13 + 17 4z = 13 + 17 Combine like terms: 13 + 17 = 30 4z = 30 Divide each side by '4'. z = 7.5 Simplifying z = 7.5
| (.50)x=4 | | 2y+3=3(y+0) | | (.50)2=4 | | -(r+s)-(2r+2s)= | | 4Z^5-8Z^3=0 | | -9y-4=31 | | 4(x+4)=x-4 | | n/2-10=88 | | 16z-48=42 | | 14z-48=42 | | -25+6x=29 | | b-8-2=11 | | -4r^2+10r+3=0 | | -4/5+7/9-3/10= | | 7(3)=4(3)+9 | | 3(4x^2-7)=5(x^2-3) | | (-p-8)-(2p-6)= | | f(x)=x^3-8x^2+30x-36 | | -6=n-14-5 | | x+(x-70)=248 | | -(x-4)=-44 | | (0.5)(-0.5)(3.2)(-7.9)(-2.4)(0)= | | -7r-3x+2=-8x+-8 | | (2y+12)=4y | | 19+6x=61 | | -7r-3x+2=-8x-8 | | 8(x+2)-3(x-4)=6(x+7)+8 | | 2(x^2-4)=2(3x^2+1) | | -11+3x=10 | | 8/9p-2/3^^^^^^^6_ | | 24+6x=78 | | 2g+8=23 |